Precursor molecules for 1,2-diamidobenzene containing cobalt(II), nickel(II) and zinc(II) complexes - synthesis and magnetic properties - Hunger, David; Suhr, Simon; Bayer, Valentin; Albold, Uta; Frey, Wolfgang; Sarkar, Biprajit; van Slageren, Joris (Dalton transactions : an international journal of inorganic chemistry, 2024)
Molecular magnetic materials based on 1,2-diamidobenzenes are well known and have been intensively studied both experimentally and computationally. They possess interesting magnetic properties as well as redox activity. In this work, we present the synthesis and investigation of potent synthons for constructing discrete metal-organic architectures featuring 1,2-diamidobenzene-coordinated metal centres. The synthons feature weakly bound dimethoxyethane (dme) ligands in addition to the 1,2-diamidobenzene. We characterize these complexes and investigate their magnetic properties by means of static and dynamic magnetometry and high-field electron paramagnetic resonance (HFEPR). Interestingly, the magnetic and magnetic resonance data strongly suggest a dimeric formulation of these complexes, . [M (bmsab)(dme)] (bmsab = 1,2-bis(methanesulfonamido)benzene; dme = dimethoxyethane) with M = Co, Ni, Zn. A large negative -value of -60 cm was found for the Co(II) synthon and an equally large negative of -50 cm for the Ni(II) synthon. For Co(II), the sign of the -value is the same as that found for the known bis-diamidobenzene complexes of this ion. In contrast, the negative -value for the Ni(II) complex is unexpected, which we explain in terms of a change in coordination number. The heteroleptic Co(II) complex presented here does not feature slow relaxation of the magnetization, in contrast to the homoleptic Co(II) 1,2-diamidobenzene complex.